THE PROBLEM OF DISCOURSE IN LINGUISTICS - Joldasova, G.B.; Klishbekova, G.A. (FAN va JAMIYAT, 2022)
The article tells about the study of discourse as a special category has developed in various independently existing and developing national schools. Because of the polysemantic nature of the concept of "discourse", it is difficult for linguists to identify its main characteristics. That is why this problem is still extremely relevant in linguistics.